Infotainment systems: Current status and future research perspectives toward 5G technologies - Gamboa Rosales, Nadia Karina; Celaya-Padilla, José María; Galván-Tejada, Carlos E.; Galván-Tejada, Jorge I.; Luna-García, Huizilopoztli; Gamboa-Rosales, Hamurabi; López-Robles, José Ricardo (Iberoamerican Journal of Science Measurement and Communication, 2022)
Objective. The objectives of this study were (1) to identify and visualize the research on infotainment systems and 5G technologies and (2) to describe their current condition based on the scientific literature through bibliometric indicators such as publication output, citations impact, authorship, and geographic distribution. Design/Methodology/Approach. The data for this study were extracted from Scopus, where the defined time coverage was 2016-2022. The methodological procedures were divided into two phases. In the first phase, we evaluated productivity and impact through bibliometric indicators. In the second one, we examined the most relevant topics in the area through bibliometric mapping using the SciMAT software. Results/Discussion. 128 research topics were identified, standing out: Signal-to-Interference-Ratio-(SIR), Vehicle-to-Vehicle-(V2V), Mobile-Security, Energy-Utilization, Mobility-Management, Resource-Allocation-Techniques, Roads-and-Streets, Vehicular-Applications, Internet-of-Things-(IoT), Intelligent-Connected-and-Autonomous-Vehicles, and Software-Defined-Networking-(SDN). A strong link between the telecommunications, mobility, and electronics sectors was evidenced, in which the vehicle was considered a deployment element. Conclusions. Infotainment systems and 5G technologies are in the process of evolution. Each technology has driven this evolution individually because of its synergy and application in vehicles. The most relevant topic within the analysis has been Vehicle-to-Vehicle-(V2V), which covers communication between vehicles and represents one of the main catalysts in the evolution of the concept of mobility. Originality/Value. This study establishes a reference framework in the field of infotainment systems and 5G technologies which are currently being deployed and consolidated.